Interlinking of rivers in India : Overview and Ken-Betwa link - "Alagh , Yoginder K (ed) ; Pangare , Ganesh (ed)" (New Delhi, 2006)
This comprehensive look at the river linking project in India provides an unbiased analysis and considers the pros and cons associated with the project, giving factual insight into how such projects can be analyzed by pointing out gaps in feasibility reporting and project planning.
Keywords: Rivers-Interlinking